Evaluasi Pelaksanaan Program Pembinaan Mahasiswa Wirausaha (P2MW) STIE Ganesha Tahun 2022 - Saefullah, Aep; Arza, Zubair; Putra, Devid; Fadli, Ahmad; Aisha, Neila (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
Three company groups made up of ten Ganesha College of Economics students took part in the Student Entrepreneurship Development Program (P2MW) Kemdikbud Ristek in 2022. Within the context of higher education, the P2MW program promotes the enhancement and development of students' entrepreneurial skills. This study intends to evaluate the P2MW implementation that took place within STIE Ganesha for 4 months, from August to November 2022. A descriptive qualitative approach is used in this study. Through observation, reading, and interviews, data were gathered and processed. P2MW had a significant favorable effect on universities, instructors, and students, according to the findings. Additionally, because they don't understand the program, supervisors and students may encounter difficulties implementing P2MW's digital reporting mechanisms. The Belmawa Kemdikbud Ristek rules ensure that P2MW STIE Ganesha's deployment is successful. Universities are urged to offer more support to instructors and students in entrepreneurship so that they are better equipped to participate in the next program.